Peripheral Artery Disease and Osteoporosis - Bilgin Bahadır Basgoz; Musa Baris Aykan; Ilker Tasci (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2017)
The frequency of peripheral arterial disease (PAD) increases with advancing age similar to that of osteoporosis [1], which is the most common bone disease worldwide and a growing public health issue for the aging population. Thus, a better understanding of osteoporosis and related problems are of utmost importance. According to World Health Organization criteria, diagnosis of osteoporosis is based on bone mineral density (BMD) values or presence of osteoporotic fractures [2].